METHODS OF DETERMINING THE PSYCHOLOGICAL READINESS FOR MILITARY PERSONNEL AT RISK - Kolesnichenko, О. S.; Matcegora, Ya. V.; Prikhodko, І. І.; Yurieva, N. V. (Honor and Law, 2019)
Psychological readiness to take risks, as a component of readiness for professional work, can be seen as a situational and long. The latter – a set of professionally important properties that can diagnose it.The study of psychological readiness for military risk it possible to determine its content, structure and levels, and became the basis for the development of psychodiagnostic methods. It has a scale: the capacity for willpower, military brotherhood, professional identity, self-control; It meets the requirements of reliability and validity.